An observational study assessing the impact of a cardiac arrest centre on patient outcomes after out-of-hospital cardiac arrest (OHCA). Issue 4 (November 2020) - Kelham, Matthew; Jones, Timothy N; Rathod, Krishnaraj S; Guttmann, Oliver; Proudfoot, Alastair; Rees, Paul; Knight, Charles J; Ozkor, Muhiddin; Wragg, Andrew; Jain, Ajay; Baumbach, Andreas; Mathur, Anthony; et al.
Background: Out-of-hospital cardiac arrest (OHCA) is a major cause of death worldwide. Recent guidelines recommend the centralisation of OHCA services in cardiac arrest centres to improve outcomes. In 2015, two major tertiary cardiac centres in London merged to form a large dedicated tertiary cardiac centre. This study aimed to compare the short-term mortality of patients admitted with an OHCA before-and-after the merger of services had taken place and admission criteria were relaxed, which led to managing OHCA in higher volume. Methods: We retrospectively analysed the data of OHCA patients pre- and post-merger. Baseline demographic and medical characteristics were recorded, along with factors relating to the cardiac arrest. The primary endpoint was in-hospital mortality. Results: OHCA patients ( N =728; 267 pre- and 461 post-merger) between 2013 and 2018 were analysed. Patients admitted pre-merger were older (65.0 vs . 62.4 years, p =0.027), otherwise there were similar baseline demographic and peri-arrest characteristics. There was a greater proportion of non-acute coronary syndrome-related OHCA admission post-merger (10.1% vs . 23.4%, p =0.0001) and a corresponding decrease in those admitted with ST-elevation myocardial infarction (80.2% vs . 57.0%, p =0.0001) and those treated with percutaneous coronary intervention (78.8% vs . 54.0%, p =0.0001). Despite this, in-hospital mortality was lower post-merger (63.7% vs . 44.3%, p =0.0001), which persisted after adjustment for demographic and arrest-related characteristics using stepwise logistic regression ( p =0.036) between the groups. Conclusion: Despite an increase in non-acute coronary syndrome-related OHCA cases, the formation of a centralised invasive heart centre was associated with improved survival in OHCA patients. This suggests there may be a benefit of a cardiac arrest centre model of care.